2023
DOI: 10.3390/pharmaceutics15030975
|View full text |Cite
|
Sign up to set email alerts
|

New Smart Bioactive and Biomimetic Chitosan-Based Hydrogels for Wounds Care Management

Abstract: Wound management represents a continuous challenge for health systems worldwide, considering the growing incidence of wound-related comorbidities, such as diabetes, high blood pressure, obesity, and autoimmune diseases. In this context, hydrogels are considered viable options since they mimic the skin structure and promote autolysis and growth factor synthesis. Unfortunately, hydrogels are associated with several drawbacks, such as low mechanical strength and the potential toxicity of byproducts released after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Except for FA-CS-oxHA, which exhibited some level of toxicity at higher concentrations, hydrogels were non-toxic; FA-CS-oxHA exhibited anti-bacterial effects against Staphylococcus aureus. Overall, the study indicated that non-toxic smart hydrogels with oxidized polymers as cross-linkers are useful for treating irregular deep wounds due to their self-healing and adapting properties [150].…”
Section: Wound Healingmentioning
confidence: 92%
“…Except for FA-CS-oxHA, which exhibited some level of toxicity at higher concentrations, hydrogels were non-toxic; FA-CS-oxHA exhibited anti-bacterial effects against Staphylococcus aureus. Overall, the study indicated that non-toxic smart hydrogels with oxidized polymers as cross-linkers are useful for treating irregular deep wounds due to their self-healing and adapting properties [150].…”
Section: Wound Healingmentioning
confidence: 92%
“…Chitosan is a natural biodegradable polysaccharide derived from chitin deacetylation. It has the same glycosaminoglycan component as ECM, apart from the ability to be biocompatible, biodegradable; it also has hemostatic, antibacterial and antifungal properties which is unique to chitosan [ 51 , 52 ]. This advantage provides faster diabetic foot ulcer recovery.…”
Section: Nanomaterials Used In Wound Dressingmentioning
confidence: 99%
“…Collagen is a vital constituent present in ECM. Collagen stimulates fibroblast migration in the damaged tissue and modulates the granulation process, helping in cell attachment and proliferation [ 51 ]. However, it is commonly combined with synthetic polymers because it is unstable at higher temperatures [ 54 ].…”
Section: Nanomaterials Used In Wound Dressingmentioning
confidence: 99%
“…CS/oxidized konjac glucomannan Silver (nanoparticles) Self-healing, self-adapting [71] Oxidized CS/bacterial cellulose -Self-healing [158] N,O-carboxymethyl CS/oxidized dextran -Self-healing, injectability [159] Quaternized CS/oxidized dextran Tobramycin Self-healing [160] Carboxymethyl CS/oxidized quaternized guaran -Self-healing [122] CS/oxidized CS Fusidic acid, alantoin, coenzyme Q10 Self-healing, self-adapting [161] CS/polyvinylpyrrolidone/alginate/ poly(ε-caprolactone) -Thermo-responsive [162] CS/poly(aspartic acid) Amoxicilin pH/thermo-responsive [163] Alginate is an anionic natural copolymer, composed of blocks of guluronate and mannuronate, obtained by alkaline extraction from brown algaes (Laminaria spp., Ascophyllumnodosum, Macrocysti spyrifera) or by microbial synthesis (Azotobacter, Pseudomonas). It is characterized by several properties, such as biocompatibility, low toxicity, economical affordable, and ease of gelation, which makes alginate attractive for biomedical applications such as tissue engineering, drug delivery, biosensing, and wound healing [164,165].…”
Section: Apis Shs Features Referencesmentioning
confidence: 99%